2016
DOI: 10.4067/s0718-58392016000300005
|View full text |Cite
|
Sign up to set email alerts
|

An accurate prediction of maize crosses using diallel analysis and best linear unbiased predictor (BLUP)

Abstract: A major obstacle in corn (Zea mays L.) breeding programs is how to obtain strains which, when combined, ensure increased productivity in all crop characteristics. Therefore, the objective of this study was to evaluate the prediction efficiency of hybrid maize using diallel analysis and the best linear unbiased predictor (BLUP). Eight synthetic varieties were sown in a diallel scheme and the hybrid and their parents were then evaluated in three separate environments; both combining ability and predicted breedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Considering GY and PE, the commercial checks obtained average predicted values of 3.42 t ha -1 and 27.18 mL g -1 , whilst the single hybrid were superiors for GY (3.68 t ha -1 ) but presented lower values for PE (22.71 L g -1 ). For GY, these values can be considered superior when compared with Vieira et al (2011) and Silva et al (2013), although, the values obtained for PE are below than those observed by Arnhold et al (2010) and Rossato Júnior et al 2013, but very similar from the data observed by authors with experimental (VIEIRA et al, 2011) and commercial (LEONELLO et al, 2009) single hybrids. The predicted values for PH and EH were similar between the single hybrids and the commercial checks, which are already established in the popcorn market.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Considering GY and PE, the commercial checks obtained average predicted values of 3.42 t ha -1 and 27.18 mL g -1 , whilst the single hybrid were superiors for GY (3.68 t ha -1 ) but presented lower values for PE (22.71 L g -1 ). For GY, these values can be considered superior when compared with Vieira et al (2011) and Silva et al (2013), although, the values obtained for PE are below than those observed by Arnhold et al (2010) and Rossato Júnior et al 2013, but very similar from the data observed by authors with experimental (VIEIRA et al, 2011) and commercial (LEONELLO et al, 2009) single hybrids. The predicted values for PH and EH were similar between the single hybrids and the commercial checks, which are already established in the popcorn market.…”
Section: Resultssupporting
confidence: 66%
“…Popcorn (Zea mays everta) is a popular snack food and it is very appreciated in Brazil, presenting higher aggregate value when compared with field corn. Popping expansion is conferred by pericarp resistance and grain moisture, differing from the field corn and being classified as specialty corn, although both belong to the same genus and species (LEONELLO et al, 2009;DE CARVALHO et al, 2013). When popcorn grains are exposed under heat, the oil and moisture content make pressure over pericarp, bursting it and exposing the endosperm, the so-called "popcorn flower".…”
Section: Introductionmentioning
confidence: 99%
“…The lines with best GCA effects and crosses with best SCA effects can be used in predicting the best performing cultivars (Technow et al, 2012;Oliveira et al, 2016). Lines with best GCAs effects are best to predict synthetics; while the crosses with best SCAs are best for predicting hybrid varieties (Malik et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The inbred lines with best GCAs for grain yield and or silking will be utilised in predicting and generating the best maize synthetic varieties (Technow et al, 2012;Oliveira et al, 2016); while the crosses with best SCAs will be used in maize hybrid development programs aiming at high yield and small silking period (Ndhlela et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation